STANDARDIZATION OF VELLARUGU CHOORANAM: A SIDDHA HERBAL DRUG - Vinotha Sanmugarajah; Thabrew, Ira; Sivapalan, Sri Ranjani (International Journal of Ayurveda and Pharma Research, 2015)
Pharmacognostical standardization of herbal formulation is essential in order to assess the quality of drugs, based on the concentration of their active principles. Vellarugu chooranam is a reputed drug mentioned in the ancient books of Siddha Medicine for the treatment of Vata diseases, arthritis, constipation, and diabetes mellitus. The main component of Vellarugu chooranam is whole plant of Enicostemma littorale Blume (Siddha Name: Vellarugu) (Gentianaceae). In the present study an attempt has been made to standardize the Vellarugu chooranam. For the standardization of this drug Organoleptic properties, Phytochemical screening, Fluorescence analysis, Elemental analysis, Physicochemical parameters such as moisture content, ash values, extractability in water and ethanol were carried out. TLC and HPLC fingerprints of the Vellarugu chooranam were also prepared to evaluate its quality. These set of parameters were found to be sufficient to evaluate authenticity of the Vellarugu chooranam and can be used as reference standards for the preparation of a standardized pharmaceutical product and further quality control researches.